2010
DOI: 10.1530/rep-10-0216
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of bone morphogenetic proteins (BMPs), their receptors and inhibin co-receptor betaglycan during bovine antral follicle development: inhibin can antagonize the suppressive effect of BMPs on thecal androgen production

Abstract: We reported previously that bone morphogenetic proteins (BMPs) potently suppress CYP17 expression and androgen production by bovine theca interna cells (TC) in vitro. In this study, real-time PCR was used to analyse gene expression in TC and granulosa cell (GC) layers from developing bovine antral follicles (1-18 mm). Abundance of mRNA transcripts for four BMPs (BMP2, BMP4, BMP6, and BMP7) and associated type I (BMPR1A, BMPR1B, ACVR1 and ACVR1B) and type II (BMPR2, ACVR2A and ACVR2B) receptors showed relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 52 publications
9
76
0
Order By: Relevance
“…Many of the signaling pathways overrepresented by these targets corresponded to growth factors putatively involved in follicular cell proliferation and steroidogenesis and prevention of premature luteinization including HGF, IGF1, TGFb, estrogen, neurotropin/TRK, PEDF, and NGF (Parrott et al 1993, Salas et al 2006, Glister et al 2010, Mani et al 2010, Garcia-Rudaz et al 2011, Chuderland et al 2013 and others involved in oocyte maturation including neuregulin, GDNF, and EGF (Conti et al 2006, Noma et al 2011, Linher-Melville & Li 2013, the fine-tune regulation of which is of key importance during the final stages of follicle development. Also present were several core cell cycle regulatory pathways (cell cycle regulation by BTG family proteins, estrogen-mediated S phase entry, and G1/S checkpoint regulation), a finding which is consistent with the notion that the development of the dominant follicle involves a substantial decrease in granulosa cell proliferation (Lussier et al 1987, Gaytan et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the signaling pathways overrepresented by these targets corresponded to growth factors putatively involved in follicular cell proliferation and steroidogenesis and prevention of premature luteinization including HGF, IGF1, TGFb, estrogen, neurotropin/TRK, PEDF, and NGF (Parrott et al 1993, Salas et al 2006, Glister et al 2010, Mani et al 2010, Garcia-Rudaz et al 2011, Chuderland et al 2013 and others involved in oocyte maturation including neuregulin, GDNF, and EGF (Conti et al 2006, Noma et al 2011, Linher-Melville & Li 2013, the fine-tune regulation of which is of key importance during the final stages of follicle development. Also present were several core cell cycle regulatory pathways (cell cycle regulation by BTG family proteins, estrogen-mediated S phase entry, and G1/S checkpoint regulation), a finding which is consistent with the notion that the development of the dominant follicle involves a substantial decrease in granulosa cell proliferation (Lussier et al 1987, Gaytan et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In the ovary, investigations on BMPs are mainly studied in the follicle of rat (Erickson & Shimasaki, 2003), cow (Glister et al, 2010) and ewe (Juengel et al, 2006). Except a solitary report by Erickson & Shimasaki (2003) on rat, no study could be found on BMPs in the CL.…”
Section: Discussionmentioning
confidence: 99%
“…(Ferrara et al, 2003;Kaczmarek et al, 2005;Bramley et al, 2005;Otrock et al, 2007). Among the ovarian factors, members of the TGF-β super family have a biological role in the folliculogenesis in the cow (Knight & Glister, 2006;Glister et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oocyte also produces BMP6 in sheep (Juengel et al, 2006b) and cattle (Hussein et al, 2005) but BMP6 did not induce cell proliferation in sheep (Juengel et al, 2006b) and had a small effect on bovine mural granulosa cells (Glister et al, 2004) and no effect on cumulus cells (Gilchrist et al, 2006). In cattle, granulosa and theca cells from small antral follicles (1-4 mm in diameter) produce BMP2, BMP4, BMP6 and BMP7 (Glister et al, 2010) whereas in sheep, as determined by in situ hybridisation, only granulosa cells of atretic follicles express BMP2. The other BMPs were not expressed by the granulosa or theca cells, although BMP4 was produced in ovarian stroma cells surrounding some follicles.…”
Section: Introductionmentioning
confidence: 98%